Least-Squares Mixed Finite Element Method for Saddle-Point Problem (Journal of Computational Mathematics, 2000)
In this paper, a least-squares mixed finite element method for the solution of the primal saddle-point problem is developed. It is proved that the approximate problem is consistent ellipticity in the conforming finite element spaces with only the discrete BB-condition needed for a smaller auxiliary problem. The abstract error estimate is derived.